2014
DOI: 10.3109/14397595.2014.950036
|View full text |Cite
|
Sign up to set email alerts
|

Everyday clinical practice in IgG4-related dacryoadenitis and/or sialadenitis: Results from the SMART database

Abstract: Objective. Immunoglobulin (Ig)G4-related disease (IgG4-RD) is a new disease entity that has only been identified this century. Clinical information is thus lacking. We established the Sapporo Medical University and Related Institutes Database for Investigation and Best Treatments of IgG4-related Disease (SMART) to clarify the clinical features of IgG4-RD and provide useful information for clinicians. Methods. Participants comprised 122 patients with IgG4-related dacryoadenitis and/or sialadenitis (IgG4-DS), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
2
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 20 publications
4
61
2
5
Order By: Relevance
“…6,7,17,26,30,32,34,35,39,40 IgG4-related orbital disease has been a popular topic recently, and multiple therapies are being offered to patients, but corticosteroids again remain the preeminent treatment for orbital and systemic IgG4-related disease. [8][9][10]13,16,18,19,24,29,31,[47][48][49] While IgG4-related disease benefits from induction and then slow taper of corticosteroid therapy, the rate of taper is individualized according to patient response. 20 This treatment scheme does not differ from that of steroid therapy for orbital inflammation of unclear etiology.…”
Section: Lack Of Targeted Therapymentioning
confidence: 99%
“…6,7,17,26,30,32,34,35,39,40 IgG4-related orbital disease has been a popular topic recently, and multiple therapies are being offered to patients, but corticosteroids again remain the preeminent treatment for orbital and systemic IgG4-related disease. [8][9][10]13,16,18,19,24,29,31,[47][48][49] While IgG4-related disease benefits from induction and then slow taper of corticosteroid therapy, the rate of taper is individualized according to patient response. 20 This treatment scheme does not differ from that of steroid therapy for orbital inflammation of unclear etiology.…”
Section: Lack Of Targeted Therapymentioning
confidence: 99%
“…The average age at onset of symptoms is 50-60 years, (37,38) but some patients can show symptoms at a younger age, and the disease can even affect children (39-41).…”
Section: Epidemiologymentioning
confidence: 99%
“…Moreover, patients with IgG4-RD usually do not have constitutional symptoms such as fever, malaise, night sweats, or weight loss (45). Malignancies were reported in 7.4% of the patients with IgG4-RD (37). Extranodal marginal zone B-cell lymphoma may occur in ocular adnexa, salivary glands, or meningeal dura up to 5 years after diagnosis of IgG4-RD (46-48).…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…It was found that glucocorticoid has efficacy in all patients with IgG4-RD, but most patients cannot discontinue steroid and require maintenance treatment [2,3]. Furthermore, relapse can easily occur with steroid tapering [4], and there are often patients who need immunosuppressants or biologic agents for disease control [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, relapse can easily occur with steroid tapering [4], and there are often patients who need immunosuppressants or biologic agents for disease control [5,6]. However, when we analyzed the patients enrolled in the SMART (Sapporo Medical University and related institutes database for investigation and best treatment for IgG4-RD) registry cohort [2], it was found that they were a fairly diverse group in their clinical features and laboratory data even though they met the comprehensive diagnostic criteria for IgG4-RD [7]. Currently, we are in the era where personalized medicine or, furthermore, precision medicine, presented by former US President Obama [8], should be the aim.…”
Section: Introductionmentioning
confidence: 99%